NEOLOGISMS IN THE ITALIAN LANGUAGE AS A SOCIOLINGUISTIC PHENOMENON - Seliverstova, Anastasiia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The continuous development of the language contributes to the emergence of new lexical units in it. The article is devoted to neologisms of Italian language. During the last time, a lot of new neological units appeared in the Italian language, which was due to the development of new technical terms or lexical units of social networks. Pretty often there are words in the language with a synonymous meaning, but borrowings and neologisms make the description more accurate or modern. The article describes studying the sociolinguistic aspect of Italian neologisms. The peculiarities of the classification of neologisms are indicated, and the options of the origin of neologisms are given. It is also noted that some neologisms are borrowed from English or other languages, while others are formed using word formation methods. The article examines two main groups of neologisms – combinatorial and semantic. The examples for each of the groups are given and explained. Moreover, it is mentioned how neologisms appear in dictionaries and become official lexical units._____________References:• Yakovenko, O. I. Doslidzhennya problemy vyznachennya ponyattya “termin”. Movni i konceptual`ni kartyny svitu 14, 263 n. 2 [Study of the problem of defining the concept of "term". Linguistic and conceptual pictures of the world] (2004): 274–277.• Accademia della Crusca, https://accademiadellacrusca.it/it/lingua-italiana/parole-nuove/ (Дата звернення10.2023).• Adamo, Giovanni e Valeria Della Valle. Le parole del lessico italiano (Roma: Carocci, 2018).• Adamo, , Della Valle, V., Neologismi, Ist. Enciclopedia Italiana (Vicenza, 2009).• Cardinale,  Neologia e neologismi nell'Italia che cambia. Il Mulino (2021), 240.• Dardano, М., Trifone, Р. Grammatica italiana (Bologna, Zanichelli, 1995):• De Mauro, Tullio. Grande dizionario della lingua italiana, http://www.gdli.it/• L’Enciclopedia Italiana (дата звернення 23/09/2023),• Lo Zingarelli – Zanichelli – Vocabolario della Lingua Italiana (Zanichelli Editore S.P.A., 2013),• Zingarelli, https://dizionaripiu.zanichelli.it/cultura-e-attualita/le-parole-del-giorno/parola-del-giorno/amicizia• Zolli,  Come nascono le parole italiane (Milano, Rizzoli Libri S. p. A, 1989), 226.• https://www.iliesi.cnr.it/ONLI/entrata.php?id=16006• https://www.treccani.it/vocabolario/fotoshoppare_%28Neologismi%29/• https://www.treccani.it/enciclopedia/twitterare_%28altro%29/
Keywords: neologism, neologism unit, borrowing, semantic neologisms, combinatorial neologisms